(untitled) (Bangladesh Journal of Agricultural Research, 2019)
The experiment was conducted at the field and laboratory of the Department of Crop Botany, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur during the period from December 2016 to March 2017 to find out the morpho-anatomical appraisal of some pulse crops of Fabaceae family under salinity stress. Seven pulse crops viz., Lentil var. BARI Masur-7, Mungbean var. BARI Mung- 6, Blackgram var. BARI Maskalai-1, Chickpea var. BARI Chola-9, Field pea var. BARI Motor-1, Grasspea var. BARI Khesari-3 and Cowpea var. BARI Felon-2; two levels of salinity 0 and 8 dSm-1were imposed as experimental treatments. It was laid out in a completely randomized design with three replications. The NaCl was directly mixed to the dry soil. The soil (6 kg pot-1) of each treatment was placed in plastic pots with drainage holes in the bottom. The results of the experiment revealed that, salt stress caused decrease in morphological attributes and also changed anatomical features. There was a significant variation in relative values (%) of plant height, root length (%) root dry matter (%) and shoot dry matter (%) of seven selected pulse crop varieties due to the salinity stress. The highest percentage of relative plant height (92), relative root length (98), relative root dry weight (89) and relative shoot dry weight (72.8) were observed in cowpea followed by grass pea and the lowest percentage of relative plant height (51), relative root length (56), relative root dry weight (54) and relative shoot dry weight (48) were observed in lentil. The stem anatomical features were found similar changes in xylem and phloem area. Among the pulse crop varieties, cowpea and grass pea were performed better whereas lentil and black gram were found more susceptible species than the others according to their morphological and anatomical attributes. Bangladesh J. Agril. Res. 44(3): 439-451, September 2019